UNSEEN EFFORTS: EXPLORING THE ROLE OF EMOTIONAL LABOR IN E-COMMERCE CUSTOMER CARE - Sullivan, Christopher Michael; Richardson, Elizabeth Anne (Ayden Journal of Management and Social Sciences, 2024)
In the ever-evolving landscape of work, the nature of jobs has witnessed significant transformations over time. The transition from the pre-industrial era, where labor primarily focused on converting calories to joules, to the industrial and subsequent service economies brought about profound changes in the workforce. The industrial revolution of the nineteenth century reshaped the job market, replacing skilled artisans with standardized and synchronized tasks in large factories. While it eliminated certain artisanal roles, it simultaneously created opportunities demanding cognitive skills and mathematical logic prowess. This shift paved the way for a service-oriented economy, further amplifying the need for cognitive labor across various roles, from arithmetic clerks to bureaucratic supervisors and decision-making managers. These positions often required individuals to acquire math-logic skills, internalize them as procedural knowledge, and apply them on demand. The demand for intellectual labor continued its ascent as the knowledge economy took center stage. Just as the division of labor transformed skilled crafts into routine tasks, and scientific management dictated the pace of work in mass production environments, the advent of computer technology ushered in new changes in job dynamics. As early as the 1960s, visionaries like Herbert Simon foresaw the potential impact of computers on the workplace. They anticipated an increase in jobs that necessitated critical thinking and low-tech services, while predicting a decline in structured, high-paying positions in manufacturing and services. Shoshana Zuboff underscored the blurring boundaries between learning and work in computer-mediated environments and advocated for an "informated" workplace that supported workers rather than merely automating their roles. This abstract delves into the evolving nature of work, highlighting historical shifts and anticipatory insights into the changing job landscape